Internet privacy rights : rights to protect autonomy - Bernal, Paul, 1964- (Cambridge University Press, 2014)
What rights to privacy do we have on the internet, and how can we make them real?
2.4 The Cybercrime Convention and the Computer Misuse Act.
Keywords: Data protection -- Law and legislation.; Computer security -- Law and legislation.; Internet -- Security measures.; Internet -- Safety measures.; Privacy, Right of.; Internet -- Sécurité -- Mesures.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; Computer security -- Law and legislation; Data protection -- Law and legislation; Internet -- Safety measures; Internet -- Security measures; Privacy, Right of; Electronic book.